Experimental Study of the Technological Process of Pressure and Speed-Based Pressure Compression of Leather Raw Material in a Multi-Operational Shaft Machine (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This paper presents experimental studies on a multi-operation shaft machine recommended for use in the leather industry. In experimental studies, taking into account three input factors, the pressure of the working shafts, the rotational speed of the working body, the angle formed by the transmission mechanism with the vertical, and the thickness of the leather raw material, a regression equation was obtained in which the output factor depends on the residual moisture. The solutions of the regression equation were obtained and analyzed graphically.